Colles’ fracture - is it a signal of osteoporosis? - Hossain, M; Hoq, MF; Fatima, N; Laskar, MH; Emran, MA; Asaduzzaman, KM; Alam, M (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):734-7 The abstract of this article is available on the PubMed website